Karakteristik Batako Pejal di Kota Manado, Bitung dan Tomohon - I Gede Yohan Kafrain; Brayen N. Palandung; Lisa S.G.E Pandean; Utarry E. Rangkang (Indonesian Journal of Fundamental Sciences, 2022)
Abstract. Bricks is still one of the walls building materials that are widely used in North Sulawesi, specifically in Manado City, Bitung City and Tomon City. The purpose of this study was to determine the characteristics of local bricks in Manado City, Bitung City and Tomohon City. The characteristics of the bricks in question are the dimensions and compressive strength of the bricks. This research was conducted by taking samples of pejal bricks from several brick production sites in Manado City, Bitung City and Tomohon City. The bricks taken to be used as samples are pressed bricks. Brick samples that have been taken from these three cities, are then tested in the laboratory. From the test results in the laboratory, it is known that for the dimensions of the brick samples taken in Manado City and Bitung City, it has not met the brick size standards based on SNI 03-0349-1989, namely the brick length of 390 mm (+3&-5), width 190 mm (+2) with a thickness of 100 mm. The bricks taken from Tomohon City for length mostly meet the existing standards with width and thickness that have not met but are close to the standard.  The results of the compressive strength test for brick samples are only brick samples in Malalayang sub-district that meet the standards, including quality IV-III of 30.67 kg / cm2. None of the brick samples taken from Bitung City and Tomohon City met the compressive strength standards. Keywords: Brick, Building Material, SNI 03-0349-1989